Factors Causing Diagnostic Delay and Treatment Delay Patient Breast Cancer in Universitas Andalas Hospital - Alfaini, Fadhli; Rafli, Rhandyka; Oktara, Meta Zulyati (Indonesian Journal of Cancer, 2024)
Background: Diagnostic and treatment delays are contributing factors to the increasing incidence and mortality of breast cancer worldwide, including in Indonesia. The study aimed to discern the underlying factors contributing to diagnostic and treatment delays in breast cancer patients.  Methods: This study uses a descriptive method. Primary data collection through guided interviews using questionnaires to 40 breast cancer patients who underwent treatment. This study was conducted at the University Andalas Hospital from January 2022 to September 2022. Results: The breast cancer diagnostic delay is caused by poor knowledge (52.5%), negative attitudes and behaviors (57.5%), a strong fear of breast cancer (55.0%), good social support (65.0%), and the impact of the Coronavirus Disease 2019 (COVID-19) pandemic on breast cancer examination (75.0%). The breast cancer treatment delay is due to poor knowledge (52.5%), positive attitudes and behaviors (52.5%), a strong fear of breast cancer treatment (55.0%), good social support (67.5%), the impact of the COVID-19 pandemic on breast cancer treatment (75.0%). Conclusions: The overview of factors causing diagnostic delay and treatment delays in breast cancer patients is dominated by negative categories, particularly in terms of knowledge, attitudes and behaviors, fear, and the COVID-19 pandemic. Only social support is positive, falling into a good category, as well as the attitudes and behaviors related to breast cancer treatment, which are also categorized as good.